ANFA – National Money Creation as an Existential Threat to the Currency Union? - Arne Hansen; Dirk Meyer (Intereconomics, 2017)
The recent publication of the previously secret Agreement on Net Financial Assets (ANFA) directed the public's attention to the possibility that national central banks could create money through purchases of securities on their own account. This paper provides an overview of the legal foundations for ANFA and shows the varying extent to which the member countries use these regulations. What are the interests, risks and consequences for the countries in crisis and the currency union as a whole? Is the ECB properly monitoring ANFA purchases? Could money creation via ANFA act as an explosive device for the currency union?
Keywords: 330